2013
DOI: 10.1130/g34045.1
|View full text |Cite
|
Sign up to set email alerts
|

Potentially induced earthquakes in Oklahoma, USA: Links between wastewater injection and the 2011 Mw 5.7 earthquake sequence

Abstract: Signifi cant earthquakes are increasingly occurring within the continental interior of the United States, including fi ve of moment magnitude (M w) ≥ 5.0 in 2011 alone. Concurrently, the volume of fl uid injected into the subsurface related to the production of unconventional resources continues to rise. Here we identify the largest earthquake potentially related to injection, an M w 5.7 earthquake in November 2011 in Oklahoma. The earthquake was felt in at least 17 states and caused damage in the epicentral r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
552
1
3

Year Published

2013
2013
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 658 publications
(601 citation statements)
references
References 11 publications
17
552
1
3
Order By: Relevance
“…However, the earthquakes were induced in the critically stressed crystalline basement and not in the sedimentary formations where wastewater was injected. Wastewater was injected into the basal aquifer, which led to the pressurization of faults in the crystalline basement (27)(28)(29). In the case of the earthquakes of Guy and Greenbrier, Arkansas, wastewater was injected into the Ozark aquifer (3 km deep), which is placed right above the crystalline basement.…”
Section: Significancementioning
confidence: 99%
“…However, the earthquakes were induced in the critically stressed crystalline basement and not in the sedimentary formations where wastewater was injected. Wastewater was injected into the basal aquifer, which led to the pressurization of faults in the crystalline basement (27)(28)(29). In the case of the earthquakes of Guy and Greenbrier, Arkansas, wastewater was injected into the Ozark aquifer (3 km deep), which is placed right above the crystalline basement.…”
Section: Significancementioning
confidence: 99%
“…The biggest earthquake ever recorded in Oklahoma was a magnitude-5.6 event near the town of Prague in November 2011, and many seismologists think that it was induced by nearby disposal wells 3 . Theoretical work 4 suggests that the potential size of a quake grows with the volume of fluid injected into the ground.…”
Section: Seismologist Amberlee Darold Is Tracking Unprecedented Earthmentioning
confidence: 99%
“…6). Thus, if one attributes the seismicity either to overpressuring reducing friction on faults, or to exceeding the capacity of "effectively sealed compartments," as Keranen et al (10) recently suggested might contribute to causing a 2011 M5.7 earthquake in Oklahoma, it is plausible that injected gas played a dominant role. This is an unusual and noteworthy instance where gas injection may have contributed to triggering earthquakes having magnitudes of 3 or larger, as the 2006-2012 sequence included 18 earthquakes with magnitudes exceeding 3, and an M W 4.4 earthquake that occurred September 11, 2011.…”
Section: H Inmentioning
confidence: 99%
“…triggered seismicity | fluid injection | carbon sequestration I nduced seismicity related to underground injection of liquids has been widely reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) but there are very few reports of gas injection triggering earthquakes large enough to be felt or cause damage at the surface. Thus, the injection-induced earthquakes of concern are not the tiny events accompanying hydrofracturing that have magnitudes of 1.5 or smaller; rather, they are the larger-magnitude earthquakes sometimes caused by injection for water flooding, enhanced production, or waste disposal.…”
mentioning
confidence: 99%